A Wide‐Bandgap Conjugated Polymer Based on Quinoxalino[6, 5‐f ]quinoxaline for Fullerene and Non‐Fullerene Polymer Solar Cells. Issue 13 (25th April 2019) - Pang, Shuting; Liu, Liqian; Sun, Xiaofei; Dong, Sheng; Wang, Zhenfeng; Zhang, Ruiwen; Guo, Yiting; Li, Weiwei; Zheng, Nan; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract: A wide‐bandgap conjugated polymer, PNQx‐2F2T, based on a ring‐fused unit of quinoxalino[6, 5‐ f   ]quinoxaline (NQx), is synthesized for use as electron donor in polymer solar cells (PSCs). The polymer shows intense light absorption in the range from 300 to 740 nm and favorable energy levels of frontier molecular orbitals. The polymer has afforded decent device performance when blended with either fullerene‐based acceptor [6, 6]‐phenyl‐C71 ‐butylric acid methyl ester ([70]PCBM) or non‐fullerene acceptor 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone‐methyl))‐5, 5, 11, 11‐tetrakis(4‐ n ‐hexylphenyl)‐dithieno[2, 3‐ d : 2′, 3′‐ d ′]‐s‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene (IT‐M). The highest PCEs of 7.9% and 7.5% have been achieved for [70]PCBM or IT‐M based PSCs, respectively. Moreover, the influence of molecular weight of PNQx‐2F2T on solar cell performance has been investigated. It is found that fullerene‐based devices prefer higher polymer molecular weight, while non‐fullerene devices are not susceptible to the molecular weight of PNQx‐2F2T. The device results are extensively explained by electrical and morphological characterizations. This work not only evidences the potential of NQx for constructing high‐performance photovoltaic polymers but also demonstrates a useful structure–performance relationship for efficiency enhancement of non‐fullerene PSCs via the development of new conjugated polymers. Abstract : A conjugated polymer, PNQx‐2F2T, based on a ring‐fused core quinoxalino[6, 5‐ f   ]quinoxaline, is synthesized. When blended with [70]PCBM or IT‐M, the solar cells of PNQx‐2F2T afford highest efficiencies of 7.9% and 7.5%, respectively. Moreover, it is found that [70]PCBM‐based devices prefer higher polymer molecular weight, while IT‐M‐based devices are not susceptible to the molecular weight of PNQx‐2F2T.